(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Multiple sclerosis (MS) is a chronic inflammatory autoimmune disease with unknown etiology. Variation in the HLA-DRB1 gene is the potent genetic risk factor for promoting MS. Other agents relate with an increased risk of developing MS include the cytokines levels such as interleukin-10 (IL-10) and the vitamin D (vit. D) deficiency. Objectives:To study a possible role of HLA-DRB1, vit. D deficiency as a risk factor for MS development and to estimate the level of IL-10 in the serum of MS patients and its role in disease initiation or progression. Methods:Sixty MS patients, of them 30 were newly diagnosed with an age range between 13 and 58 years were included in this study, in addition to thirty healthy volunteers their gender and age matched with patients group serve as a control group. Blood samples collected to assess serum levels of vit. D and IL-10 by Enzyme-Linked Immunosorbant Assay (ELISA) and for DNA extraction, which used in the HLA-DRB1 2 digit genotyping. Results :The HLA-DRB1 genotyping revealed that the HLA-DRB1*15 frequency was higher but statistically insignificant in the MS patients as compared with healthy control group. IL-10 level was significantly lower in MS patients on treatment than the control group. On the other hand, vit. D in the newly diagnosed MS patients was significantly different from the control group (higher in the control group), but there was no variance with MS patients on treatment, the level of vit. D in the studied groups was less than global value. Conclusion:In MS patients the frequency of HLA-DRB1*15 was higher than control group but the difference was not significant. In addition, the level of IL-10 and vit. D may have a role in the development of MS. Keywords:Multiple sclerosis, human leukocyte antigen, IL-10